Social representation of university students on violence in affective-sexual relationships (Encuentros, 2022)
This study aimed to analyze the structure and content of the social representations of students residing in the student’s house about violence in affective-sexual relationships. 244 residents of the Student House of a federal university in southern Brazil participated. Data were collected between August and December 2019 by evocations with the inducing term “violence in affective-sexual relationships”. The analysis was carried out using the IRAMUTEQ software. The central terms were violence, physical and verbal violence, social judgment and disrespect. The representation appears permeated by negative elements that refer to evaluative feelings of the violent situation. The social representation of university students about violence in affective-sexual relationships has as a central element in its structure and content, violence and its main forms of occurrence.
Keywords: students; Interpersonal relationships; Nursing; Intimate partner violence; universities